Pendampingan Penyusunan LKPD berbasis Scientific Approach pada Guru Sekolah Dasar - Haryanto Haryanto; Wuri Wuryandani; Suwarjo Suwarjo; Ratna Hidayah; Vera Yuli Erviana; Ainun Mahfuzah (DEDIKASI: Community Service Reports, 2022)
Assignment to use students worksheet as an alternative teacher to support learning during a pandemic. This training activity aims to improve the ability of teachers in compiling and developing students worksheet based on the Scientific Approach in learning. This activity was carried out in collaboration with the coordinator of the Sendangtirto Cluster Elementary School, Berbah, Sleman. This activity involved 30 elementary school teachers as participants, with a training model. Data on increasing the ability of participants was obtained through a questionnaire. Based on the data obtained, there was an increase in the assessment and ability of teachers towards the preparation and use of students  worksheet based on the scientific approach after participating in this training activity into high and very high categories. After the training, participants are able to prepare students worksheet based on a scientific approach and implement it in learning.